Relationship between self-efficacy and knowledge sharing: systematic review. Issue 3 (29th April 2020) - Safdar, Muhammad; Batool, Syeda Hina; Mahmood, Khalid
Abstract : Purpose: The purpose of this paper was to systematically collect and review the research studies that provide empirical evidence regarding the existence of relationship between self-efficacy and knowledge sharing or influence of self-efficacy on sharing of knowledge. Design/methodology/approach: The studies were collected through searching in Google Scholar, Scopus, ProQuest Dissertations and Theses, LISTA (Library, Information Science and Technology Abstracts) and Web of Science. All types of studies, except books, were selected for review. Time limitation was not applied. Findings: It can be concluded from majority of reviewed studies that self-efficacy influenced knowledge sharing. This systematic review also establishes that majority of reviewed studies confirmed existence of relationship (positive) between variables self-efficacy and knowledge sharing. Research limitations/implications: A language limit was applied, and only English language studies were reviewed. Originality/value: This review is first of its kind that systematically collected and reviewed the studies that examined the relationship between self-efficacy and knowledge sharing. This paper is also first in terms of a study which systematically collected and reviewed studies that investigated impact of self-efficacy on sharing of knowledge. Findings of current research paper will be helpful for organizations striving to implement a knowledge-sharing culture. Similarly, this study will also help the readers in understanding the ways to improve their knowledge-sharing practices and learning.